Assessment of government incentives for energy from waste in Colombia (2018)
ABSTRACT: This work evaluates the prefeasibility of energy from waste projects in Colombia under the guidelines of Law 1715. That piece of legislation proposes tax incentives for non-conventional energy initiatives, such as deductions of up to 50% on the investment through income tax, VAT exemption, tariff exemption, and accelerated depreciation of assets. Pasto, Colombia, was selected as the case study. Subsequently, incineration, gasification, anaerobic digestion, and landfill gas technologies were evaluated. The potential of electric power generation from municipal solid waste (MSW) of each conversion technology was estimated with mathematical models. Additionally, the economic evaluation considered five cases that combine loan options, accelerated depreciation, and income deductions. Finally, the prefeasibility analysis of each case and technology was based on the internal rate of return (IRR) and levelized cost of electricity (LCOE). The results reveal that only anaerobic digestion and landfill gas technologies constitute viable projects in case of traditional investment with and without loans, because they present IRRs greater than the discount rate, of 6.8%. However, by including the incentives in Law 1715 in the economic evaluation, IRRs of 11.18%, 7.96%, 14.27%, and 13.59% were obtained for incineration, gasification, anaerobic digestion, and landfill gas, respectively. These results make all four technologies feasible in this context.